Parenting: awareness about the own educative role and citizen competences - Umberto Margiotta; Elena Zambianchi (Pensa MultiMedia, 2014)
It is since a long time that the European Community highlights how parents - fundamental resource for the education of the "tomorrow' citizens" - must be supported in the interpretation of their educative role and in the assumption of their whole responsibility with respect to the related functions. This paper presents the results of an ALICE pilot project dedicated to the training of parents with children aged 0-3 and realized as a laboratory of reflection through creative and informal languages. It comes to a formative proposal relative to empowerment interventions, aimed at sustaining parent competences and its conscious use from an educational point of view. Each meeting was organised in two phases: (a) self-reflection as parent and then as son/daughter; (b) realization of creative activities to enhance the educational quality of the relationship with their children. The participation of parents has been constantly active. The feedback obtained through a satisfaction survey and a questionnaire for self-evaluation to compare pre- and post- training has been very satisfactory.